A Splenic Artery Aneurysm Occlusion by Overlapping Gore® Viabahn® Endoprosthesis Devices - Nando Mertineit; Amgad El Mekabaty; Gholam Reza Afarideh; Carlos Buitrago Tellez; Pascal Kissling; Stefanie Garni; Frank Mosler; Gerd Nöldge (Swiss Journal of Radiology and Nuclear Medicine)
The first lienal artery aneurysm was discovered and described for the first time in 1770 by the Frenchman Beaussier during an autopsy. It was first visualised using X-rays in 1920 by the physicians Akbulut and Otan. The first surgical treatment of a splenic artery aneurysm was performed by sur-geons MacLeod and Maurice in 1940. The first minimally invasive endovascular therapies using coils, stents or a combination of the two devices for minimally invasive treatment of aneurysms of the lienal artery were reported in 1990, 1994 and 1995 (1,2,3). 63-year-old patient with a known aneurysmal arteriopathy of the thoracic aorta in the sense of an aortic dissection in coexistence with a 2.2 cm splenic artery aneurysm discovered by chance in the vascular surgery department of the Bürgerspital Solothurn. The interdisciplinary consensus primarily favoured vascular surgery or minimally invasive transcatheter treatment to eliminate the splenic artery aneurysm. The dissected thoracic aortic aneurysm detected in the pre-interventional CT of the thorax and abdomen, extending into the abdominal aorta, (Fig. 1) should only be treated with minimally invasive endovascular treatment using EVAR after stenting of the lienal artery aneurysm detected by CT (Fig. 9, 10, 11). A reverse therapeutic sequence would have allowed access to the lienal artery aneurysm only by fenestration of the EVAR. For the treatment of our patient's wide-neck aneurysm, the use of a Viabahn was chosen from the many known and proven occlusion materials as a significantly less invasive alternative to surgical treatment of the aneurysm by interdisciplinary consensus. Due to a technical complication during the deployment of the first vial, a two-stage angiographic therapeutic intervention was necessary.